2002
DOI: 10.1002/car.727
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two programmes for victims of child sexual abuse: a treatment outcome study

Abstract: This study aimed to evaluate the comparative effectiveness of individual therapy and combined individual and group therapy in the treatment of the psychological sequelae of child sexual abuse. The Child Behaviour Checklist (CBCL), the Youth Self Report form (YSR), the Children's Depression Inventory (CDI) and the Trauma Symptom Checklist for Children (TSCC) were administered before treatment and 6 months later to a group of 20 young people who participated in individual therapy (IT) programmes and to a group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 15 publications
1
47
0
7
Order By: Relevance
“…Of the seven studies [174][175][176][177][178][179][180] evaluating psychotherapy/counselling, five studies 174-178 measured psychological distress outcomes, all but one 174 measured behaviour outcomes, five studies [175][176][177][178] looked at cognitive outcomes, and one study 177 looked at placement stability. One study 175 reported on the intervention's acceptability.…”
Section: Psychotherapy/counsellingmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the seven studies [174][175][176][177][178][179][180] evaluating psychotherapy/counselling, five studies 174-178 measured psychological distress outcomes, all but one 174 measured behaviour outcomes, five studies [175][176][177][178] looked at cognitive outcomes, and one study 177 looked at placement stability. One study 175 reported on the intervention's acceptability.…”
Section: Psychotherapy/counsellingmentioning
confidence: 99%
“…Four 155,174,178,179 studies assessed the effectiveness of psychotherapy without clearly describing their theoretical underpinnings. One 178 study explored the value added of group psychotherapy when added to individual psychotherapy.…”
Section: Psychotherapy/counsellingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a small proportion of CSA survivors come into contact with assessment and treatment services Carr, 1999c, Nolan et al, 2002b;Nolan et al, 2002a). The effects, both short and long-term, of CSA on psychological functioning have been well documented.…”
Section: Introductionmentioning
confidence: 99%